2022
DOI: 10.1007/s12471-022-01705-8
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the effect of advance care planning implementation on healthcare utilisation and satisfaction in patients with advanced heart failure

Abstract: Background Patients with advanced heart failure may benefit from palliative care, including advance care planning (ACP). ACP, which can include referral back to the general practitioner (GP), may prevent unbeneficial hospital admissions and interventional/surgical procedures that are not in accordance with the patient’s personal goals of care. Aim To implement ACP in patients with advanced heart failure and explore the effect of ACP on healthcare utilisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…After the intervention, 21 patients (78%) indicated that they would not want to be readmitted and were thus not readmitted during the follow-up period, and 12 patients (40%) died at home during the follow-up period. 19 A South Korean study noted that the tendency to select hospice care was positively correlated with attitude toward ACP. 5 Therefore, ACP can affect EOL treatment decisions among patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the intervention, 21 patients (78%) indicated that they would not want to be readmitted and were thus not readmitted during the follow-up period, and 12 patients (40%) died at home during the follow-up period. 19 A South Korean study noted that the tendency to select hospice care was positively correlated with attitude toward ACP. 5 Therefore, ACP can affect EOL treatment decisions among patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot study, an ACP intervention was conducted with 30 patients with New York Heart Association functional class III or IV heart failure who had experienced at least 1 unexpected hospitalization in the previous year. After the intervention, 21 patients (78%) indicated that they would not want to be readmitted and were thus not readmitted during the follow-up period, and 12 patients (40%) died at home during the follow-up period 19 . A South Korean study noted that the tendency to select hospice care was positively correlated with attitude toward ACP 5 .…”
Section: Discussionmentioning
confidence: 99%